A problem with logarithms.

Algebra Level 3

If log b ( a b c ) = 1 \log_{b} \left ( \dfrac{a}{bc} \right ) = 1 , then find the value of log b ( c a b ) \log_{b} \left(\dfrac{c}{ab} \right) .


The answer is -3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Ravneet Singh
Dec 6, 2017

log b ( a b c ) = 1 \log_{b} \left ( \dfrac{a}{bc} \right ) = 1

a b c = b \implies \dfrac{a}{bc} = b

a = b 2 c \implies a = b^2c

log b ( c a b ) = log b ( c b 3 c ) = log b ( 1 b 3 ) = 3 \log_{b} \left(\dfrac{c}{ab} \right) = \log_{b} \left(\dfrac{c}{b^3 c} \right) = \log_{b} \left(\dfrac{1}{b^3} \right) = \boxed{-3}

log b a b c = 1 log b a log b b log b c = 1 log b a 1 log b c = 1 log b a log b c = 2 . . . ( 1 ) \begin{aligned} \log_b \frac a{bc} & = 1 \\ \log_b a - \log_b b - \log_b c & = 1 \\ \log_b a - 1 - \log_b c & = 1 \\ \color{#3D99F6} \log_b a - \log_b c & \color{#3D99F6} = 2 & \color{#3D99F6} ...(1) \end{aligned}

Then,

log b c b a = log b c log b b log b a = log b c 1 log b a = ( log b a log b c ) 1 Note ( 1 ) : log b a log b c = 2 = ( 2 ) 1 = 3 \begin{aligned} \log_b \frac c{ba} & = \log_b c - \log_b b - \log_b a \\ & = \log_b c -1 - \log_b a \\ & = - \left({\color{#3D99F6}\log_b a - \log_b c}\right) - 1 & \small \color{#3D99F6} \text{Note }(1): \log_b a - \log_b c = 2 \\ & = - \left({\color{#3D99F6}2}\right) - 1 \\ & = \boxed{-3} \end{aligned}

Mark Jones
Dec 5, 2017

l o g b ( a b c ) = l o g b ( a c ) + l o g b ( 1 b ) = l o g b ( a c ) 1 = 1. log_{b} \left ( \frac{a}{bc} \right ) = log_{b} \left ( \frac{a}{c} \right ) + log_{b} \left ( \frac{1}{b} \right ) = log_{b} \left ( \frac{a}{c} \right ) - 1 = 1. l o g b ( a c ) = 2. \therefore log_{b} \left ( \frac{a}{c} \right ) = 2. l o g b ( c a ) = 2. log_{b} \left ( \frac{c}{a} \right ) = -2. l o g b ( c a b ) = 2 1 = 3. log_{b} \left ( \frac{c}{ab} \right ) = -2 - 1 = -3.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...